Cycle ergometer 페달회전율에 따른 임계파워와 유·무산소성 능력과의 관련성 - 김의영(Eui Young Kim); 김성연(Sung Yeon Kim); 조은형(Eun Hyung Cho) (한국체육측정평가학회지, 2011)
본 연구는 사이클 에르고메터 페달회전율에 따른 임계파워와 유⋅무산소성 능력 간에 관계를 알아보고 페달회전율이 변수산정에 미치는 영향을 규명하기 위하여 20대 초반의 건강한 남성 20명을 대상으로 사이클 에르고메터를 이용하여 4.0-8.5 W/kg의 운동강도에서 1-10분 이내에 탈진에 이르는 에르고메터 운동을 55rpm과 70rpm에서 4회 수행하여 임계파워와 무산소성 작업능력을 측정하였다. 무산소성 능력을 측정하기 위하여 윈게이트 검사를 하였고, 유산소성 능력을 측정하기 위하여 트레드밀을 이용하여 운동부하검사를 실시하였다. 연구결과 임계파워는 70rpm 결과에서 그리고 무산소성 작업능력은 55rpm에서 측정한 결과에서 유의하게 높게 나타났다. 페달회전율에 따른 임계파워와 유⋅무산소성 능력과의 관계는 55rpm에서 산출한 임계파워는 유산소성 능력인 최대산소섭취량(r=.557, p＜.01), 역치환기량(r=-.481, p＜.05), 최대심박수(r=-.462, p＜.05)와 유의한 상관관계를 나타내었으며, 무산소성 능력인 PP(r=.728, p＜.01), FI(r=.719,p＜.01), MP(r=.660, p＜.01), TW(r=.660, p＜.01) 순으로 유의한 상관관계를 나타내었고, 70rpm에서 산출한 임계파워는 유산소성 능력인 최대산소섭취량(r=.606, p＜.01)과 유의한 상관관계를 나타내었으며, 무산소성 능력인 PP(r=.767, p＜.01), MP(r=.753, p＜.01), TW(r=.753, p＜.01), FI(r=.519, p＜.05) 순으로 유의한 상관관계를 나타내었다. 이상의 결과에 의하면 사이클 에르고메터를 이용하여 임계파워를 측정할 때 페달회전율이 측정결과에 영향을 미치는 것으로 나타나 연구자들은 페달회전율 선택에 좀 더 신중을 기해야 할 것으로 사료된다. The purpose of this study was to verify potential correlations of critical power with aerobic and anaerobic exercise performance depending on pedal revolution per minute of cycle ergometer, and determine potential effects of pedal revolution per minute on calculation of variables. In order to meet these purposes, this study used cycle ergometer to test the critical power and anaerobic work capacity of 20 young healthy male adults in their early 20’s. In this test, they were asked to take 4 sessions of cycle ergometer exercise at 2 different revolutions 55 rpm and 70 rpm respectively and at such an exercise intensity ranging from 4.0 to 8.5 W/kg as they could feel exhausted not longer than 1 to 10 minutes. All subjects were asked to take Wingate Test to measure their anaerobic exercise performance. Moreover, they were also asked to take exercise stress test while running on treadmill in order to measure their aerobic exercise performance. As a result, it was found that they reached significantly high critical power at 70 rpm, but they reached significantly high anaerobic work capacity at 55 rpm. According to analysis on potential correlations of critical power with aerobic and anaerobic exercise performance depending on pedal revolution of cycle ergometer, it was found that critical power measured at 55 rpm was significantly correlated with aerobic exercise performance factors such as maximum oxygen uptake (r=.557, p＜.01), ventilatory threshold (r=-.481, p＜.05) and maximum heart rate (r=-.462, p＜.05) respectively, and was also significantly correlated with anaerobic exercise performance factors such as PP (r=.728, p＜.01), FI (r=.719,p＜.01), MP (r=.660, p＜.01) and TW (r=.660, p＜.01) respectively. In addition, it was found that critical power measured at 70rpm was significantly correlated with maximum oxygen uptake (r=.606, p＜.01) as a factor of aerobic exercise performance, and was also significantly correlated with anaerobic exercise performance factors such as PP (r=.767, p＜.01), MP (r=.753, p＜.01), TW (r=.753, p＜.01) and FI (r=.519, p＜.05) respectively. Based on these findings, it is concluded that pedal revolution per minute has effects on critical power measured with cycle ergometer. Hence, it is required that follow-up studies should be more careful in selection of pedal revolution than this study. KCI Citation Count: 2